Robotic Compartment-Based Radical Surgery in Early-Stage Cervical Cancer. (18th April 2016) - Toptas, Tayfun; Uysal, Aysel; Ureyen, Isin; Erol, Onur; Simsek, Tayup
Abstract : A radical hysterectomy with pelvic lymphadenectomy is the recommended treatment option in patients with early-stage cervical cancer. Although various classifications were developed in order to define the resection margins of this operation, no clear standardization could be achieved both in the nomenclature and in the extent of the surgery. Total mesometrial resection (TMMR) is a novel procedure which aims to remove all components of the compartment formed by Müllerian duct in which female reproductive organs develop. TMMR differs from the conventional radical hysterectomy techniques in that its surgical philosophy, terminology, and partly resection borders are different. In this paper, a TMMR with therapeutic pelvic lymphadenectomy operation that we performed for the first time with robot-assisted laparoscopic (robotic) approach in an early-stage cervical cancer patient was presented. This procedure has already been described in open surgery by Michael Höckel and translated to the robotic surgery by Rainer Kimmig. Our report is the second paper, to our knowledge, to present the initial experience regarding robotic TMMR in the English literature.